Analysis of the image of political leader in extent considerations of contemporary Ukrainian students - Andrieieva, Yaroslava; Lytovchenko, Nina (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2019)
The article is devoted to the socio-psychological analysis of the image of a political leader in the space of thinking of Ukrainian student youth. The problems of the implementation of the political choice of student youth in the process of socio-political changes are revealed. As politics began to be perceived as personalized, through the prism of personal characteristics of particular political figures, it is relevant to study the role of the image of a political leader, which is characterized by the transformation of personal and professional qualities.The paper presents a comparative analysis of the results of an empirical study of the image of a political leader in the space of thinking of student youth conducted at the Nizhyn Mykola Gogol State University and Yuriy Fedkovych Chernivtsi National University in 2011-2019. The article presents that formed image of the politician determines the level of political activity during elections. A comparative analysis of the results obtained concerning the priorities of student youth reveals the most important political quality of the political leader for student youth – his social orientation and concern for the people. The results of the comparative analysis indicate an increase in the political subjectivity of youth, but negative emotions (disappointment) impede the willingness for responsible participation in political life. Three groups of factors are identified that mediate the process of perception by the electorate of a political leader. Features of vertical and horizontal involvement of a citizen in political activity are revealed. The peculiarities of changing attitudes and the value-normative orientation of the political consciousness of modern students are demonstrated.
Keywords: political conscience; a subject to social-political activity; political activity; political leader; political choice; student youth